Study on the Adsorption Behavior of a Cellulose Nanofibril/Tannic Acid/Polyvinyl Alcohol Aerogel for Cu(II), Cd(II), and Pb(II) Heavy Metal Ions - Xuejin Zhang; Yulong Tian; Huanhuan Chen; Ying Liu; Shuaichuang Han; Minmin Chang; Jingshun Zhuang; Qingzhi Ma (Nanomaterials)
Nanocellulose-based composite aerogels have the advantages of high porosity, biodegradability, and biocompatibility, with wide applications in many fields, such as adsorption, separation, energy storage, and heat insulation. In this study, a nanocellulose-based composite aerogel (NCA) was prepared using the one-pot method with cellulose nanofibrils (CNFs), tannic acid (TA), and polyvinyl alcohol (PVA) as raw materials. The adsorption behaviors of Pb2+, Cd2+, and Cu2+ were also studied. FT-IR analysis confirmed that TA successfully solidified on the nanocellulose, while SEM analysis revealed that the prepared NCA exhibited significantly higher porosity compared with the cellulose nanofibril-only aerogel. The results of the adsorption experiment demonstrated that the adsorption behavior of heavy metal ions using the prepared NCA followed pseudo-second-order kinetics. The adsorption isotherms fit well with the Langmuir adsorption model, indicating that the process of aerogels adsorbing heavy metal ions is that of monolayer adsorption. Under conditions of pH 6 and an initial heavy metal ion concentration of 100 mg/L, the maximum adsorption capacity calculated for the prepared NCA was up to 196.850 mg/g, 181.488 mg/g, and 151.515 mg/g for Cu2+, Cd2+, and Pb2+, respectively. Furthermore, the prepared NCA exhibited excellent reusability, with more than 90% efficiency retained after three cycles. NCAs have the potential to become an efficient material for absorbing heavy metal ions in water.